PENGARUH RESILIENSI TERHADAP PSYCHOLOGICAL WELL-BEING PADA GENERASI SANDWICH - Frangky Franscois; Meiske Yunithree Suparman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to understand the effect of resilience on psychological well-being in the sandwich generation. The sandwich generation consists of individuals who bear dual responsibilities: caring for elderly parents while meeting the needs of their own nuclear family. This study used a quantitative method with data collected through a questionnaire involving 223 productive-age respondents. The Resilience Scale (RS-14) and Ryff’s Scales of Psychological Well-Being were used to measure the resilience and psychological well-being levels of the respondents. The results showed that resilience has a significant positive effect on psychological well-being in the sandwich generation, with a contribution of 37.8%. This finding indicates that individuals with high resilience tend to have better psychological well-being. Thus, increasing resilience could be an effective strategy for managing the pressures faced by the sandwich generation. This study contributes to a deeper understanding of the importance of resilience in supporting the psychological well-being of the sandwich generation.